The Salão da Bússola (1969) and Do Corpo à Terra (1970): Parallel Developments in Brazilian and International Art - Brodbeck, Anna (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2013)
Brazilian artists of the 1960s and 1970s were deeply engaged with their own modernist legacy, especially in relation to European models that had fascinated the cultural scene since the 1920s. Following in the spirit of Oswald de Andrade’s “Manifesto Antropófago” (1928), which argued that artists in Brazil should aggressively devour imported source material as a means of creating something unique to their country, Brazilian artists and critics during this period sought to define their relationship to international modern art. This essay examines two exhibitions. The first, the Salão da Bússola (1969), revealed the emergence of “anti-art” characterized by bodily performance and the use of “poor” materials. The second, Do Corpo à Terra (1970), more clearly defined the Brazilian response to the burgeoning movements of “post-studio” art such as arte povera, process art, and land art. The curatorial efforts and critical response to these exhibitions reveal a deliberate positioning of such experiments with regard not only to contemporary artists such as Jan Dibbets, but also to historical vanguard artists such as Kurt Schwitters and Kazimir Malevich. Taking up both the legacy of the European avant-garde and contemporary local concerns, Brazilian artists at this time effectively answered Andrade’s call to create art that was born of Brazil but walking in step with international art.